2016
DOI: 10.1021/acs.jpcc.5b12423
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postsynthesis Purifications on Gold and Silver Nanoparticle Ligand Coverage

Abstract: Wet chemical nanoparticle synthesis is commonly employed because of the ability to tailor and control nanoparticle size, shape, polydispersity, and surface chemistry; however, excess ligands or free surfactants in the colloidal dispersion can be detrimental for many nanoparticle applications. Postsynthesis purification using antisolvent precipitation is a widely employed method to remove the excess ligands or precursors; however, there has been little in-depth fundamental investigation of the dynamics between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 44 publications
2
43
0
Order By: Relevance
“…This size selective precipitation allows for collecting NPs with similar sizes and discarding extremely small NPs (Figure 1.2.9) 17 . It is worth to note here that the use of excess methanol should be avoided, since this will coprecipitate excess ligand molecules in solution along with the collected NPs, and thus hinder the purification 18 . Synthesis of Au NPs in presence of decanoic acid: Decanoic acid-stabilized Au NPs ( 7 nm core diameter): For this purpose, a solution of 43 mg (250 µmol) decanoic acid (Sigma Aldrich, #C1875) dissolved in 2.5 mL toluene, and a solution of 25 mg (97.2 mmol) TBAB dissolved in 1 mL DDAB stock solution (100 mM in toluene) were added in a 25 mL flask.…”
Section: Figure I25 Purification Of Toab-au Nps Upper Toluene Phamentioning
confidence: 99%
See 1 more Smart Citation
“…This size selective precipitation allows for collecting NPs with similar sizes and discarding extremely small NPs (Figure 1.2.9) 17 . It is worth to note here that the use of excess methanol should be avoided, since this will coprecipitate excess ligand molecules in solution along with the collected NPs, and thus hinder the purification 18 . Synthesis of Au NPs in presence of decanoic acid: Decanoic acid-stabilized Au NPs ( 7 nm core diameter): For this purpose, a solution of 43 mg (250 µmol) decanoic acid (Sigma Aldrich, #C1875) dissolved in 2.5 mL toluene, and a solution of 25 mg (97.2 mmol) TBAB dissolved in 1 mL DDAB stock solution (100 mM in toluene) were added in a 25 mL flask.…”
Section: Figure I25 Purification Of Toab-au Nps Upper Toluene Phamentioning
confidence: 99%
“…Purification on the other hand also may change the properties of the NPs, e.g. modify their ligand shell 18 .…”
Section: Vii1 General Considerationsmentioning
confidence: 99%
“…Reported strategies for the controlled formation of monolayers are mainly based on the introduction of bulky protecting groups. 8 We have developed a different strategy that relies on the grafting of calix [4]arenes bearing diazonium groups at their large rim. 9 Thanks to the well pre-organized and 3D conic structure of the calix [4]arene core, densely packed monolayers and mixed binary monolayers were obtained on flat surfaces, with a good control of the surface composition and a high homogeneity of the deposit.…”
mentioning
confidence: 99%
“…8 We have developed a different strategy that relies on the grafting of calix [4]arenes bearing diazonium groups at their large rim. 9 Thanks to the well pre-organized and 3D conic structure of the calix [4]arene core, densely packed monolayers and mixed binary monolayers were obtained on flat surfaces, with a good control of the surface composition and a high homogeneity of the deposit. 10 Provided that the small rim of the calix [4]arene is decorated with appending reactive arms, like carboxylic groups, the immobilized calix [4]arene moieties can be easily post-functionalized with various molecules.…”
mentioning
confidence: 99%
“…They showed that by altering the molar ratio between the ligand (dodecanethiols) and the gold salt (HAuCl 4 ), and even the temperature or the rate at which the reduction is conducted, AuNPs between 1.5 and 5.2 nm can be synthesized. Since then, many different modifications of the two‐phase Brust–Schiffrin method focusing on different sizes by altering ligand/Au ratio were published as well as by altering the pH‐value . In addition, the work of Hussain et al .…”
Section: Introductionmentioning
confidence: 99%